Incorporating climate change adaptation into marine protected area planning. (19th April 2020) - Wilson, Kristen L.; Tittensor, Derek P.; Worm, Boris; Lotze, Heike K.
Abstract: Climate change is increasingly impacting marine protected areas (MPAs) and MPA networks, yet adaptation strategies are rarely incorporated into MPA design and management plans according to the primary scientific literature. Here we review the state of knowledge for adapting existing and future MPAs to climate change and synthesize case studies ( n = 27) of how marine conservation planning can respond to shifting environmental conditions. First, we derive a generalized conservation planning framework based on five published frameworks that incorporate climate change adaptation to inform MPA design. We then summarize examples from the scientific literature to assess how conservation goals were defined, vulnerability assessments performed and adaptation strategies incorporated into the design and management of existing or new MPAs. Our analysis revealed that 82% of real‐world examples of climate change adaptation in MPA planning derive from tropical reefs, highlighting the need for research in other ecosystems and habitat types. We found contrasting recommendations for adaptation strategies at the planning stage, either focusing only on climate refugia, or aiming for representative protection of areas encompassing the full range of expected climate change impacts. Recommendations for MPA management were more unified and focused on adaptative management approaches. Lastly, we evaluate common barriers to adopting climate change adaptation strategies based on reviewing studies which conducted interviews with MPA managers and other conservation practitioners. This highlights a lack of scientific studies evaluating different adaptation strategies and shortcomings in current governance structures as two major barriers, and we discuss how these could be overcome. Our review provides a comprehensive synthesis of planning frameworks, case studies, adaptation strategies and management actions which can inform a more coordinated global effort to adapt existing and future MPA networks to continued climate change. Abstract : We reviewed the state of knowledge for adapting existing and future marine protected areas (MPAs) to climate change and synthesized case studies ( n = 27) on how MPA planning can respond to shifting environmental conditions. We identified several research topics that warrant further investigation, including focusing on multiple ecosystem types across a range of latitudes, and gathering empirical evidence to build an understanding of the effectiveness of different adaptation strategies.